Host specificity and uniqueness of shell microbiome in freshwater mollusks - Zhao, Zifan; Mao, Zhendu; He, Dan; Wang, Heng; Wu, Qinglong (Frontiers in Microbiology, 2025)
IntroductionMollusk shells represent a major substrate for the colonization of microbial communities and the functioning of aquatic ecosystems. However, our knowledge of the shell microbiome is very limited.MethodsHere, we selected Bellamya aeruginosa and Corbicula fluminea as two types of snails and clams, respectively, to explore their shell epiphytic bacteria by 16S amplicon sequencing.ResultsWe found different shell bacterial communities between snails and clams, which were also distinct from those in the surrounding environment. Source tracking analysis indicated that snail-shell bacteria were mostly derived from sediments, whereas clamshells originated from tissues. There was a site-specific difference in the shell bacteria within the habitat. Temporal variation in clamshell bacteria was observed, but not in snail shells, which corresponds to their source dynamics in the water column and stable surface sediment bacterial communities, respectively. The genus Nitrospira is mostly enriched in shell bacteria, particularly in eutrophic lakes. Taxa related to carbon, nitrogen, and sulfur cycling were recognized as the keystone species in the co-occurrence network associated with the shell surface. Our results demonstrate that mollusk shells represent a unique ecological niche for microbiomes in aquatic ecosystems and may serve as hotspots for biogeochemical cycling.